2021
DOI: 10.3390/ijerph182111688
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Professional Soccer Players before and after COVID-19 Infection; Observational Study with an Emphasis on Graduated Return to Play

Abstract: The impact of the COVID-19 pandemic in sport has been the subject of numerous studies over the past two years. However, knowledge about the direct impact of COVID-19 infection on the performance of athletes is limited, and the importance of studies on this topic is crucial during the current pandemic era. This study aimed to evaluate the changes in the match running performance (MRP) of professional soccer players that occurred as a result of COVID-19 infection after fulfilling all of the prerequisites for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…There were nine studies reporting acute (short‐term) effects of acute respiratory infection (ARinf) on exercise performance outcomes (Table 2). In these studies, outcome variables were determined immediately after the ARinf (<2 days) (Weidner, Anderson, Kaminsky, Dick, & Schuur, 1997) within 10 days of the ARinf (Fricker et al, 2005), <30 days (Costello et al, 2021; Csulak et al, 2021; Fikenzer et al, 2021; Komici et al, 2021; Savicevic et al, 2021; Wagemans et al, 2021) or >30 days (Anastasio et al, 2021; Crameri et al, 2020; Wagemans et al, 2021) in the studies investigating SARS‐CoV‐2 infection specifically. In one study, it was not reported how long after the ARinf episode the data were collected (Vaudreuil, Kennedy, Lombardo, & Kharrazi, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were nine studies reporting acute (short‐term) effects of acute respiratory infection (ARinf) on exercise performance outcomes (Table 2). In these studies, outcome variables were determined immediately after the ARinf (<2 days) (Weidner, Anderson, Kaminsky, Dick, & Schuur, 1997) within 10 days of the ARinf (Fricker et al, 2005), <30 days (Costello et al, 2021; Csulak et al, 2021; Fikenzer et al, 2021; Komici et al, 2021; Savicevic et al, 2021; Wagemans et al, 2021) or >30 days (Anastasio et al, 2021; Crameri et al, 2020; Wagemans et al, 2021) in the studies investigating SARS‐CoV‐2 infection specifically. In one study, it was not reported how long after the ARinf episode the data were collected (Vaudreuil, Kennedy, Lombardo, & Kharrazi, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In three of these studies the diagnosis of ARinf was suspected and the pathogen/s not identified, while in the other three studies SARS‐CoV‐2 infection was confirmed. The sports performance outcome variables were training modifications (Csulak et al, 2021; Fricker et al, 2005; He et al, 2013), match performance (Savicevic et al, 2021; Vaudreuil et al, 2021), or a change in standardised points (Csulak et al, 2021; Pyne et al, 2000). The main findings are conflicting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, comparing the number of medals won between the athletes who tested positive and those who did not, the period of forced detraining due to the restriction imposed by the RTP protocol did not negatively affect the athlete’s performance. A recent study investigating the performance of professional soccer players before and after COVID-19 showed that it took approximately 3 weeks for asymptomatic and 4–6 weeks for symptomatic players to return to the level of performance preceding the infection 25. With a mean detraining period of 30±13 days, athletes with a previous infection who were allowed to resume physical activity and selected for the Olympics did not win fewer medals than COVID-19– subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Speaking more specifically about soccer teams, the publications on COVID and soccer often focus on particular aspects such as the impact of quarantine or COVID on team sports performance [18,19,[46][47][48] or the psychological impact of the pandemic on players and their families [33,49]. There are reports on the change in sporting outcomes caused by pandemic conditions, such as a lower win ratio when playing in stadiums without a crowd [17, [50][51][52][53][54] and FIFA regulations during the pandemic [55][56][57].…”
Section: Discussionmentioning
confidence: 99%